Homogenization of long-term GPS monitoring series at permanent stations in Central Europe and Balkan Peninsula - HEFTY, Ján; IGONDOVÁ, Miroslava; DROŠČÁK, Branislav (Contributions to Geophysics and Geodesy, 2009)
The  network   of  54  permanent  GPS  stations situated  in  Central   Europe, Alpine-Adriatic region  and  Balkan Peninsula is analyzed by  uniﬁed  processing strategy, using  homogeneous models  for reduction of physical eﬀects,  and  is uniformly referred to as the International Terrestrial Reference  Frame  – ITRF2005.  The resulting time series  of observed site  coordinates and site  troposphere parameters from interval 1999.5 to 2008.5 are inspected for their  continuity, homogeneity, long-term  drift,  and seasonal variations.